2007
DOI: 10.1007/s11207-007-0263-1
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of RHESSI Flares Using aRadio Astronomical Technique

Abstract: We have used Ramaty High Energy Solar Spectroscopic Imager (RHESSI) modulation profiles in the 25 -300 keV range to construct high-fidelity visibilities of 25 flares having at least two components. These hard X-ray visibilities, which are mathematically identical to the visibilities of radio imaging, were input to software developed for mapping solar flares in the microwave domain using the Maximum Entropy Method (MEM). We compared and contrasted the MEM maps with Clean and Pixon maps made with RHESSI software… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
86
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(91 citation statements)
references
References 9 publications
5
86
0
Order By: Relevance
“…They instead prefer a magnetic mirroring model (Melrose & Brown 1976) in which the magnetic field converges more quickly at one of the footpoints. This convergence of the magnetic field lines has been found to be consistent with area measurements of HXR footpoints (Schmahl et al 2006) and has been observed in one M-class limb event with RHESSI (Kontar et al 2008).…”
Section: Introductionsupporting
confidence: 86%
“…They instead prefer a magnetic mirroring model (Melrose & Brown 1976) in which the magnetic field converges more quickly at one of the footpoints. This convergence of the magnetic field lines has been found to be consistent with area measurements of HXR footpoints (Schmahl et al 2006) and has been observed in one M-class limb event with RHESSI (Kontar et al 2008).…”
Section: Introductionsupporting
confidence: 86%
“…4 (left). To better quantify the size of the X-ray source, the visibility forward fitting technique was also used (see Schmahl et al 2007 for the definition of visibilities; and Xu et al 2008 for examples of application). This algorithm allows the size of the source to be computed and also the error on the size once a model has been chosen.…”
Section: Temporal and Spatial Evolution Of The X-ray Emissionsmentioning
confidence: 99%
“…Dennis & Pernak (2009) and Kontar et al (2010) have pointed out that CLEAN images usually have systematically larger sizes than other algorithms when using the default beam width factor of 1.0. To ensure the best possible determination of the source sizes using CLEAN images, we applied the visibility forward-fitting procedure (Schmahl et al 2007) on the footpoints of each flare, adjusted the CLEAN beam size, and re-calculated the images until the FWHM of the footpoint from both algorithms had the same size. The integration time interval …”
Section: Imaging Spectroscopymentioning
confidence: 99%
“…We emphasize that the inference of imaging spectroscopy parameters relies strongly on the precise knowledge of the X-ray source area, which was only developed fairly recently (e.g. Schmahl et al 2007;Kontar et al 2008;Dennis & Pernak 2009;Kontar et al 2010). In addition, the full Spectral Response Matrix (SRM) of RHESSI detectors (including non-diagonal terms) for imaging spectroscopy became available relatively recently, since 2006 February.…”
Section: Introductionmentioning
confidence: 99%